Seasonal variation in species composition, deltamethrin susceptibility, and kdr mutations in anopheles mosquitoes in Northwest Ethiopia - Ligabaw Worku; Amha Kebede; Ayalew Jejaw Zeleke; Saron Fekadu; Melat Abdo; Tigist Atele; Netsanet Worku; Mulugeta Aemero (PLoS ONE, 2026)
Background Anopheles mosquitoes are the main vectors of malaria. Effective vector control depends on understanding their species composition, behavior, distribution, and insecticide resistance. This study investigated Anopheles species composition, susceptibility to deltamethrin, and the frequency of knockdown resistance ( kdr ) mutations in Maksegnit and Gendawuha, Northwest Ethiopia. Methods Anopheles larvae and pupae were collected from breeding sites during the rainy and post-rainy seasons and reared to adults under field insectary conditions following WHO guidelines. In addition, adult mosquitoes were collected from houses near larval habitats. Only field-derived mosquito populations were used in this study. Adult females (3–5 days old) reared from field-collected larvae were tested for susceptibility to 0.05% deltamethrin using WHO bioassays. Based on bioassay outcomes, mosquitoes were classified as phenotypically susceptible (died after exposure) or resistant (survived exposure), while field-collected adults represented an unexposed group. A total of 480 mosquitoes (160 resistant, 160 susceptible, and 160 field-collected unexposed adults) were subjected to genomic DNA extraction. Species identification and detection of knockdown resistance ( kdr ) mutations (L1014F and L1014S) were performed using PCR. Results WHO bioassays conducted on 776 mosquitoes revealed confirmed resistance to deltamethrin, with mortality rates ranging from 48.5% to 72.5% (overall resistance: 37.5%). Resistance intensity exhibited significant variation, peaking after the rainy season and showing a higher prevalence in Maksegnit compared to Gendawuha (p < 0.05). Molecular identification of 480 mosquitoes showed that Anopheles arabiensis was the predominant species (93%, 446/480), followed by An. pharoensis (6%, 29/480) and An. stephensi (1%, z/480), with the latter detected for the first time in Gendawuha. Regarding kdr mutation status, genotypic analysis showed that the L1014F mutation was the predominant allele, particularly among phenotypically resistant mosquitoes (67.8%), while lower frequencies were observed in susceptible (45.8%) and unexposed field-collected groups (61.4%). Conversely, the L1014S mutation was detected at low frequency (≤12.3%) and was restricted exclusively to the Maksegnit population. Conclusion Anopheles arabiensis predominated, with confirmed resistance to deltamethrin, particularly in the post-rainy season. The L1014F kdr mutation was prevalent, while L1014S kdr mutation was rare. Detection of Anopheles stephensi highlights emerging risks, underscoring the need for season-specific resistance monitoring and integrated control strategies .